2003
DOI: 10.1124/jpet.102.047977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ursodeoxycholic Acid on the Impairment Induced by Maternal Cholestasis in the Rat Placenta-Maternal Liver Tandem Excretory Pathway

Abstract: We investigated the effects of ursodeoxycholic acid (UDCA; 60 g/day/100 g b.wt.) on the impairment induced by maternal obstructive cholestasis during pregnancy (OCP) in the rat placentamaternal liver tandem excretory pathway. A blunted catheter was implanted in the common bile duct on day 14 of pregnancy, and the tip was cut on day 21. [ 14 C]Glycocholate (GC) was then administered through the umbilical artery of "in situ" perfused placenta (placental transfer test) or through the maternal jugular vein (biliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 40 publications
2
53
0
5
Order By: Relevance
“…The available data for the rat orthologues Mrp1, Mrp2, Mrp3 and Mrp4 suggest that they have similar expression patterns as those described for human isoforms [68] . Moreover, it has been observed that, at least in rats, there is a strong up-regulation of these transporters during maternal cholestasis, which can contribute to the protection of the fetus against the high concentrations of bile acids and biliary pigments existing on the maternal side of the placenta under these circumstances [68] .…”
Section: Excretion Of Bile Acidsmentioning
confidence: 90%
See 3 more Smart Citations
“…The available data for the rat orthologues Mrp1, Mrp2, Mrp3 and Mrp4 suggest that they have similar expression patterns as those described for human isoforms [68] . Moreover, it has been observed that, at least in rats, there is a strong up-regulation of these transporters during maternal cholestasis, which can contribute to the protection of the fetus against the high concentrations of bile acids and biliary pigments existing on the maternal side of the placenta under these circumstances [68] .…”
Section: Excretion Of Bile Acidsmentioning
confidence: 90%
“…Under normal physiological circumstances, mRNA expression levels at term were low for Oatp1a1, Oatp1b4 and Oatp1b2, but high for Oatp4a1 [42] . However, maternal cholestasis induces an up-regulation of these transporters, which is further enhanced when pregnant rats are treated with UDCA [68] . In addition, Oatp2b1 is also present in rat placenta and its ability to transport taurocholate has been described [69] .…”
Section: Excretion Of Bile Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies using experimental models of maternal cholestasis in rats [17] have reported an impairment in the placental transfer of bile acids due to trophoblast atrophy and a lack of apical membrane microvilli. This damage was partially prevented by UDCA administration [18].…”
Section: Introductionmentioning
confidence: 96%